Prevalence and Pattern of Skin Manifestations in COVID-19 Patients; A Cross-Sectional Observational Study in Saudi Arabia - Attia, Mostafa; Mahfouz, Mohammad Eid; Almalki, Khaled; Almalki, Nada; Alabbasi, Sahar; Alharthi, Atheer (International Journal of Innovative Research in Medical Science, 2021)
Background: Although COVID-19 is known to cause fever and an array of respiratory symptoms, the disease has recently been reported to be associated with dermatological symptoms. It is crucial to identify the frequency and the nature of these symptoms to facilitate the early detection and the efficient management of the disease. Methods: A cross-sectional observational survey study that was carried out in Saudi Arabia Previously-infected adult residents with COVID-19 were considered. Sociodemographic characteristics, concomitant medications, medical history, and the occurrence of skin manifestations while having COVID-19 infection were collected. Data were represented in the form of frequencies (number of responders) and valid percentages for categorical variables. ANOVA test was utilized to compare means between different subgroups. All P values < 0.05 were considered statistically significant. Result: A total of 464 participants were included. Gender distribution was almost equal. Out of them, 54.1% aged from 21 to 40 years old and 65.9% hold a university degree. Skin symptoms were reported in 9.1% respondents. The most common locations were all-over the body (1.5%), arms (1.3%), face or upper body (1.3%) and fingers (1.3%). Participants experienced morbilliform rash (3.5%), maculopapular rash (1.3%), urticaria (0.9%), livedo reticularis (0.2%) while 5.4% experienced miscellaneous skin symptoms. Conclusion: More research studies investigating the prevalence and patterns of skin symptoms accompanying COVID-19 infection are suggested.